2023
DOI: 10.3389/fonc.2023.1130911
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals differences in cell cycle, growth and migration related genes that distinguish fibroblasts derived from pre-invasive and invasive breast cancer

Abstract: Background/IntroductionAs the most common form of pre-invasive breast cancer, ductal carcinoma in situ (DCIS) affects over 50,000 women in the US annually. Despite standardized treatment involving lumpectomy and radiation therapy, up to 25% of patients with DCIS experience disease recurrence often with invasive ductal carcinoma (IDC), indicating that a subset of patients may be under-treated. As most DCIS cases will not progress to invasion, many patients may experience over-treatment. By understanding the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…This contrasts with IBC studies, where fibroblasts, and CAFs in particular, are associated with poor prognosis 3438 . Recent studies suggested fibroblast abundance in DCIS contribute to invasive progression 39,40 . Importantly, none of these studies included race as a factor in the analyses.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with IBC studies, where fibroblasts, and CAFs in particular, are associated with poor prognosis 3438 . Recent studies suggested fibroblast abundance in DCIS contribute to invasive progression 39,40 . Importantly, none of these studies included race as a factor in the analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer-associated fibroblasts facilitate premetastatic niche formation through lncRNA SNHG5-mediated angiogenesis and vascular permeability in breast cancer[ 10 ]. High expression of TGF-a, PKMYT1 and decreased SFRP1 and SFRP2 in the fibroblasts were associated with disease recurrence, invasive disease or decreased survival[ 11 ]. Hence, it is critical to explore the physiological properties of CAFs and their potential as therapeutic targets in BC.…”
Section: Introductionmentioning
confidence: 99%